Label-Free Quantitative Proteomic Analysis of the Global Response to Indole-3-Acetic Acid in Newly Isolated Pseudomonas sp. Strain LY1 - Zhao, Shuxue; Chen, Xi; Sun, Qianshu; Wang, Fei; Hu, Chunhui; Guo, Lizhong; Bai, Jie; Yu, Hao (Frontiers in Microbiology, 2021)
Indole-3-acetic acid (IAA), known as a common plant hormone, is one of the most distributed indole derivatives in the environment, but the degradation mechanism and cellular response network to IAA degradation are still not very clear. The objective of this study was to elucidate the molecular mechanisms of IAA degradation at the protein level by a newly isolated strain Pseudomonas sp. LY1. Label-free quantitative proteomic analysis of strain LY1 cultivated with IAA or citrate/NH4Cl was applied. A total of 2604 proteins were identified, and 227 proteins have differential abundances (DAPs) in the presence of IAA, including 97 highly abundant proteins and 130 less abundant proteins. Based on the proteomic analysis an IAA degrading (iad) gene cluster in strain LY1 containing IAA transformation genes (organized as iadHABICDEFG), genes of the β-ketoadipate pathway for catechol and protocatechuate degradation (catBCA and pcaABCDEF) was identified. The iadA, iadB, and iadE-disrupted mutants lost the ability to grow on IAA, which confirmed the role of the iad cluster in IAA degradation. Degradation intermediates were analyzed by HPLC, LC-MS, and GC-MS analysis. Proteomic analysis and identified products suggested that multiple degradation pathways existed in strain LY1. IAA was initially transformed to dioxindole-3-acetic acid, which was further transformed to isatin. Isatin was then transformed to isatinic acid or catechol. An in-depth data analysis suggested oxidative stress in strain LY1 during IAA degradation, and the abundance of a series of proteins was upregulated to respond to the stress, including ROS scavenging, protein repair, fatty acid synthesis, RNA protection, signal transduction, chemotaxis, and several membrane transporters. The findings firstly explained the adaptation mechanism of bacteria to IAA degradation.